2021
DOI: 10.1007/s00068-021-01778-x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture fixation in extremity trauma with carbon fiber-reinforced polyetheretherketone (CFR-PEEK) plates: evidence today

Abstract: Purpose To compare the CFR-PEEK plates with conventional plates in fracture fixation with regards to clinical and radiological outcomes and complications. Methods A systematic literature search was conducted in four online databases independently by two reviewers using the Cochrane methodology for systematic reviews. The identified relevant studies were assessed against predetermined inclusion/exclusion criteria. Independent data extraction and assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…PEEK applications in orthopedics continue to grow, with just a couple being in fracture fixation [ 24 , 25 , 26 ] and commercialized dental implants such as VESTAKEEP PEEK. PEEK is one of several polymers that has been investigated for scaffold application in BTE, some of which include PCL [ 27 , 28 ], Polyurethane [ 29 ], and PLA [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEEK applications in orthopedics continue to grow, with just a couple being in fracture fixation [ 24 , 25 , 26 ] and commercialized dental implants such as VESTAKEEP PEEK. PEEK is one of several polymers that has been investigated for scaffold application in BTE, some of which include PCL [ 27 , 28 ], Polyurethane [ 29 ], and PLA [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing use of CF plates for fixating traumatic and (impending) pathological fractures, reported experience in the literature remains limited. Previous systematic reviews have primarily focused on comparative studies or specifically examined traumatic distal radius fracture fixation with CF plates [ 11 13 ]. In these studies, CF plates were considered as a valid alternative due to comparable results to metal plates [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews have primarily focused on comparative studies or specifically examined traumatic distal radius fracture fixation with CF plates [ 11 13 ]. In these studies, CF plates were considered as a valid alternative due to comparable results to metal plates [ 11 13 ]. However, cohort studies and case reports have identified several disadvantages associated with CF plates that were not mentioned in the aforementioned systematic reviews.…”
Section: Introductionmentioning
confidence: 99%
“…We have had the pleasure of reviewing your work on the subject. 1 Overall there is no available moderate or high certainty evidence to support the use of CFR-PEEK (CFRP) implants. 2 We respectfully disagree that "all levels in the hierarchy of research methods (evidence pyramid) are inherently biased".…”
mentioning
confidence: 99%
“…The data for this location only comprises 53 patients in total from comparative analyses which precludes robust assessment of implant effects. Although the proportion of open and periprosthetic fractures may be similar, there are so few in the CFRP arm and so many in the conventional arm it is quite plausible that these more complex fractures drove some of the estimates (Table 2 from Chloros et al 1 ). A CFRP plate can also introduce a substantially different rigidity and thus stress force across the implant and total knee arthroplasty (TKA) which may alter outcomes.…”
mentioning
confidence: 99%